2015
DOI: 10.4081/or.2015.6028
|View full text |Cite
|
Sign up to set email alerts
|

Are electrically induced muscle cramps able to increase the cramp threshold frequency, when induced once a week?

Abstract: The cramp threshold frequency (CTF) is known to be positively correlated with the individual cramp susceptibility. Here we assessed CTF changes after two bouts of electrically induced muscle cramps (EIMCs). The EIMCs (6×5 sec) were unilaterally induced twice (separated by one week) in the gastrocnemius of an intervention group (n=8), while 5 participants served as control. The CTF increased from 25.1±4.6 Hz at baseline to 31.4±9.0 Hz and 31.7±8.5 Hz 24 h after bout 1 and 2 (P<0.05). Thereafter, the CTF decline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 28 publications
3
17
0
Order By: Relevance
“…However, the durability of those effects remain unclear as the longest follow‐up period after such an intervention ended 96 hours after the last cramp training session. In a more recent study we found that a single bout of EIMCs only resulted in a short‐term increase of the CTF with a peak at 24 hours after the intervention . A second bout that was applied 1 week later was not able to further increase the CTF values but induced a very similar response pattern, when compared to the first bout.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…However, the durability of those effects remain unclear as the longest follow‐up period after such an intervention ended 96 hours after the last cramp training session. In a more recent study we found that a single bout of EIMCs only resulted in a short‐term increase of the CTF with a peak at 24 hours after the intervention . A second bout that was applied 1 week later was not able to further increase the CTF values but induced a very similar response pattern, when compared to the first bout.…”
Section: Introductionmentioning
confidence: 78%
“…Using a handheld battery‐powered myostimulator (Cefar Compex, Compex 3 Professional, Compex Médical SA, Ecublens VD), the gastrocnemii of the participants were stimulated in a seated position with their legs hanging down freely. As described previously the stimulation protocol of the applied cramp training consisted of three sets of six stimulation trains that lasted for 5 sec each, interrupted by 10 sec breaks. The stimulation amplitude was set to 85% of the maximally tolerated stimulation current (mTSC), which was tested prior to every cramp training.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…How muscle cramps affect future cramp propensity is unknown, and our study does not provide clarity in this regard. However, muscle cramps are painful injuries that affect maximum force production and may even elicit some degree of muscle damage (as indicated by increases in creatine kinase and muscle soreness) . Evidence from well‐designed experimental and cohort studies suggests pain may play a role in cramp genesis.…”
Section: Discussionmentioning
confidence: 99%
“…The CTF of the calf muscles receiving stimulation in a shortened position was increased significantly at 3 ( P < 0.001) and 6 ( P < 0.001) weeks, whereas no significant changes were noted at either assessment point in the contralateral legs of the intervention participants or in the calf muscles of participants in the control group. In a follow‐up study, Behringer et al . found that 2 bouts of electrically induced muscle cramps (EIMC), induced 1‐week apart in the gastrocnemius of an intervention group ( n = 8), raised the CTF significantly for 24 hours in each of the 2 bouts ( P < 0.05).…”
Section: Treatment and Preventionmentioning
confidence: 99%